Works well with others : an outsider's guide to shaking hands, shutting up, handling jerks, and other crucial skills in business that no one ever teaches you - McCammon, Ross (New York : Dutton 1852, 2015)
"Esquire editor and Entrepreneur etiquette columnist Ross McCammon delivers a funny and authoritative guide that provides the advice you really need to be confident and authentic at work, even when you have no idea what's going on. Ten years ago, before he got a job at Esquire magazine and way before he became the etiquette columnist at Entrepreneur magazine, Ross McCammon, editor at an in-flight magazine, was staring out a second-floor window at a parking lot in suburban Dallas wondering if it was five o'clock yet. Everything changed with one phone call from Esquire. Three weeks later, he was working in New York and wondering what the hell had just happened. This is McCammon's honest, funny, and entertaining journey from impostor to authority, a story that begins with periods of debilitating workplace anxiety but leads to rich insights and practical advice from a guy who "made it" but who still remembers what it's like to feel entirely ill-equipped for professional success. And for life in general, if we're being completely honest. McCammon points out the workplace for what it is: an often absurd landscape of ego and fear guided by social rules that no one ever talks about. He offers a mix of enlightening and often self-deprecating personal stories about his experience and clear, practical advice on getting the small things right--crucial skills that often go unacknowledged--from shaking a hand to conducting a business meeting in a bar to navigating a work party. Here is an inspirational new way of looking at your job, your career, and success itself; an accessible guide for those of us who are smart, talented, and ambitious but who aren't well-"leveraged" and don't quite feel prepared for success. or know what to do once we've made it. "--
Includes index.
Keywords: Business -- Humor; Business etiquette -- Humor; HUMOR / Topic / Business & Professional